Validating the “Two Faces” of Envy: The Effect of Self-Control - Yang, Chen; Tang, Rixin (Frontiers in Psychology, 2021)
Envy drives different behaviors, and while we often emphasize the negative effects of envy, there are also relatively positive aspects. This study explored the “two faces” of envy or behaviors that improve oneself or degrade others. In study 1 (N=466, 45.1% males and 54.9% females; Mage=18.53, SDage=2.05), we modeled the effects of envy and self-control on effort and aggression. In study 2 (N=102, 51% males and 49% females; Mage=20.56, SDage=1.88), we explored the influence of envy on striving behavior and aggressive behavior using an ego depletion paradigm. The different effects of envy on different levels were doubly verified. We established structural equation models of the interactions of benign envy, malicious envy, self-control, and associated behaviors, and we found that: (1) Individuals’ striving behavior was only affected by benign envy; (2) Individuals’ aggressive behavior was influenced by both malicious envy and self-control. Ego depletion moderated the effect of malicious envy on aggressive behavior.